Experiences in Chinese Class for Indonesian Elementary Students in Taiwan - Margaretha Aurelia Pasaribu; Nadi Suprapto (Studies in Learning and Teaching, 2020)
This qualitative research was motivated by our experiences while being an international student in Taiwan. We met with four Indonesian students who move to Taiwan because of their parents are postgraduate students. They were four elementary students who were studying in a primary school in Hualien County as a research participant. They have been in Taiwan for around six months. Through an in-depth interview and documentation study, we captured their experiences during a Chinese class. Finally, we got three main themes that impress us: “I don’t want to be a loser! (First Impression)”; “I prefer she use body language than English (Learning Process and Teacher)”; and “If I don’t know him/her I will ask payment for me (Motivation in Chinese)”.